2019
DOI: 10.1088/1757-899x/603/2/022095
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Soil Temperature in the Modeling of Early-Age Mass Concrete Slab

Abstract: Modeling the structural behavior of concrete at early ages is one of the most challenging, yet fundamental, tasks for civil engineers working on mass concrete. To obtain a reasonably accurate model, a number of factors should be taken into account. Considerations should include both external influences as well as the changes occurring in the complex structure itself. The modeling of an early-age concrete massive slab requires the proper assignment of initial conditions, including the initial temperature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The initial temperature of each layer of the slab as well as the ambient temperature were taken based on the measurements ( Figure 2 ). The initial temperature profile in the subsoil, presented in ( Figure 5 , was determined based on the preliminary FE analysis [ 33 , 45 ]. The total time of the performed analysis was 28 days.…”
Section: The Scope and Data For Fe Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial temperature of each layer of the slab as well as the ambient temperature were taken based on the measurements ( Figure 2 ). The initial temperature profile in the subsoil, presented in ( Figure 5 , was determined based on the preliminary FE analysis [ 33 , 45 ]. The total time of the performed analysis was 28 days.…”
Section: The Scope and Data For Fe Simulationmentioning
confidence: 99%
“…Therefore, it has been examined how the vertical and horizontal sizes of the subsoil interfere with the obtained thermal and stress results. The vertical dimension of the subsoil was evaluated in the preliminary FE study [ 33 , 45 ]. The results showed that a depth of 10 m is sufficient and does not affect the temperature and stress distributions in the slab.…”
Section: The Scope and Data For Fe Simulationmentioning
confidence: 99%
See 1 more Smart Citation